4 - Skills Development in the Multinational Corporate Sector: Building Employee Capacity Beyond the Factory Gate - Joseph O. Jiboku,; Wilson Akpan, (African Sociological Review, 2019)
The dearth of skills for socio – economic transformation in Africa partly explains the drive by African countries to attract investments by multinational corporations (MNCs). The quest for skills has also been fuelled by the challenges posed by a fast globalising world economy. However, while the literature is replete with analyses of liberal policies and incentives offered to encourage investment by multinational corporations, little scholarly attention appears to have been paid to the need to incorporate MNC skills policies and programmes into the national skills agenda, and vice versa. Nigeria offers an example of how nearly a century of MNC operations has not resulted in any meaningful acquisition of strategic, as opposed to merely high level, skills by national employees. Skills disparities abound between local and expatriate employees within the same MNC operations. It is against this backdrop that this paper examines the discourse on multinational corporations and skills development and makes a case for the incorporation of multinational skills policies and strategies into the national skills development pathway, and vice versa, in line with the broader objectives of national human capital development. The paper’s central argument is that skills development must go beyond empowering employees to be ‘useful’ only within the context of a given company’s industrial operations. It is based on interviews conducted with managers and employees in selected multinational companies as well as with government agencies concerned with skills development in Nigeria.